Art as Resistance: The Role of Visual Arts in Indonesia's Struggle for Social and Political Justice (Indonesian Art and Justice Review, 2025)
In Indonesia, visual arts have long served as a powerful tool for resistance, challenging state policies, human rights abuses, and social inequalities. This paper critically examines how Indonesian artists have used their work to resist oppression, critique government policies, and highlight issues such as corruption, religious intolerance, and environmental destruction. Drawing from the work of contemporary artists involved in activism, the study analyzes the role of visual art in social movements, and how art becomes a means of protest, solidarity, and a vehicle for social justice. By focusing on specific movements or art forms such as protest art, political murals, and exhibitions, the paper underscores art's role as a vehicle for public discourse, activism, and social transformation in Indonesia.